Handbook of religion and the Asian city: aspiration and urbanization in the twenty-first century - Veer, Peter van der (University of Californiarnia Press, 2015)
In place of ritual : global city, sacred space, and the Guanyin Temple in Singapore / Daniel PS Goh -- The city and the pagoda : Buddhist spatial tactics in Shanghai / Francesca Tarocco -- Territorial cults and the urbanization of the Chinese world : a case study of Suzhou / Vincent Goossaert -- Global and religious : urban aspirations and the governance of religions in Metro Manila / Jayeel Serrano Cornelio -- The Muharram procession of Mumbai : from seafront to cemetery / Reza Masoudi Nejad -- Urban processions : colonial decline and revival as heritage in postcolonial Hong Kong / Joseph Bosco -- Urban megachurches and contentious religious politics in Seoul / Ju Hui Judy Han -- Good thoughts, good words, and good (trust) deed : Parsis, risk, and real estate in Mumbai / Leilah Vevaina -- Urban development and heritage contestation of Bangkok Chinatown / Tiamsoon Sirisrisak -- Dealing with the dragon : urban planning in Hanoi / Tam TT Ngo -- Contested religious space in Jakarta : negotiating politics, capital, and ethnicity / Chang Yau Hoon -- Urban Buddhism in the Thai post-metropolis / James Taylor -- From village to city : Hinduism and the Hindu caste system / Nathaniel Roberts -- The politics of de-secularization : Christian churches and North Korean migrants in Seoul / Jin-Heon Jung -- Parallel universes : Chinese temple networks in Singapore, or, What is missing in the Singapore model? / Kenneth Dean -- The flexibility of religion : Buddhist temples as multi-aspirational sites in contemporary Beijing / Gareth Fisher -- Cultivating happiness : psychotherapy, spirituality, and well-being in a transforming urban China / Li Zhang -- Other Christians as Christian others : signs of new Christian populations and the urban expansion of Seoul / Nicholas Harkness -- Aspiring in Karachi : breathing life into the City of Death / Noman Baig -- Can commodities be sacred? : material religion in Seoul and Hanoi / Laurel Kendall -- Cinema and Karachi in the 1960s : cultural w